UPAYA INDONESIA MENDAFTARKAN SENI PEMBUATAN KAPAL PINISI KEDALAM INTANGIBLE CULTURAL HERITAGE UNESCO - Mairering, Ruth Octavia; Putri, Penny Kurnia; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2020): Hubungan Internasional Vol1, No1, th 2020, 2020)
ABSTRACT   This research aims to describe how the Indonesian government's efforts to register the Pinisi boatbuilding art as Intangible Cultural Heritage from UNESCO using descriptive qualitative methods. Joko Widodo's regime voice the nation's maritime power through the agenda of Indonesia as the world's maritime nexus by five main pillars which are development focus, one of them is maritime tourism. As an archipelagic country, Indonesia has a legacy in the nation's historical heritage as maritime country. The legacy itself is a traditional Pinisi boat by the Bugis, a South Sulawesi tribe. Pinisi officially became a part of UNESCO Intangible Cultural Heritage on December 7th, 2017. Therefore, this research used the concept of Intangible Cultural Heritage to analyze the Art of making Pinisi boat and Multi-Track Diplomacy to analyze what diplomacy track are used to support the registration process. Keywords : Pinisi Boat, Intangible Cultural Heritage, Multi-Track Diplomacy and UNESCO